Weird, wacky science - Markle, Sandra 1946-; Schoberle, Cecile Illustrator (New York : Scholastic, 1999)
Presents facts revealing some of the strange and even weird aspects of humans, animals, and general science while also suggesting experiments related to this information.
Keywords: Kids; Human body